Simultaneous determination of tocols, γ-oryzanols, phytosterols, squalene, cholecalciferol and phylloquinone in rice bran and vegetable oil samples - Piramon Pokkanta (2018)
© 2018 Elsevier Ltd In this study, a simultaneous analytical method of tocols, γ-oryzanols, phytosterols, squalene, cholecalciferol and phylloquinone were developed using HPLC-DAD-FLD. The developed method allowed the quantification of 18 compounds in 30 min. Method validation showed linearity of calibration curves (α = 0.05). RSD of intra-day, inter-day and inter-laboratory precision were less than 4.88%. The limit of detections (LODs) and limit of quantifications (LOQs) were low (0.009–2.166 μg g−1) with recoveries around 96.0–102.9%. Results derived from the established method demonstrated a wide variation of detected compounds in rice bran and vegetable oil samples (22.4–1774.6 μg g−1tocols, ND–26484 μg g−1γ-oryzanols, ND–12655 μg g−1phytosterols, ND–3189 μg g−1squalene, ND–105.3 μg g−1cholecalciferol, and ND–54.4 μg g−1phylloquinone). Thus, the developed HPLC-DAD-FLD method is a powerful analytical tool for the above mentioned compounds useful in food and pharmaceutical application.